The Effects of Turmeric Powder Addition in Fish Feed toward Hematology of Common Carp (Cyprinus carpio (Jurnal Natur Indonesia, 2022)
Turmeric (Curcuma longa) contains curcumin that can be used to improve the health as well as the immune system of the fish. The health and immune system condition of the fish can be predicted based on the hematology of the fish. A study that aims to understand the effects of turmeric addition in fish feed pellets on the hematology condition of common carp has been conducted from March to May 2022. The turmeric powder was mixed well with the feed pellets and the dosages of the turmeric powder were as follows: 0 (Control, no turmeric addition), P1 (0.5 g/kg), P2 (1 g/kg), and P3 (1.5 g/kg). The fish was reared in circular plastic containers (25 L), completed with an aerator and circulation pump) for  49 days, 15 fish/ container. During the research, the fish was fed 3 times/ day, at satiation. Samplings were conducted 2 times before the treatment was applied and by the end of the experiment (the 49th day). Results show that the addition of turmeric powder in the fish feed pellets clearly affects the hematological of the fish. Fish that was fed with turmeric-enriched pellets showed a higher percentage of lymphocyte and which means that the immunity of the fish is improved. The best treatment P3 showed 81.55% lymphocyte, 6.55% monocyte, 5.44% neutrophil, and 5.44% thrombocyte. Data obtained indicate that the fish fed with turmeric pellets perform better in hematological conditions than the fish with no turmeric-enriched pellets.